Identification of typical marker proteins of Treponema pallidum in compact human bone using morphological and biochemical techniques - Tyede H. Schmidt Schultz; Michael Schultz (Scientific Reports)
Abstract In ancient human compact bone tissue, we can present the identified marker proteins of Treponema pallidum, the lipoproteins 47 kDa, 17 kDa and 15 kDa in three adult individuals from Austria (thirteenth–seventeenth century CE), and in a 5 to 6-years-old child from Germany (seventeenth–nineteenth century CE). These three identified lipoproteins are also used to diagnose syphilis in current medicine. The individuals selected for this study predominantly exhibit the macroscopic and microscopic features of treponemal disease. However, the result of the proteomic analysis can confirm the diagnosis of treponematosis without any doubt. The extracellular matrix (ECM) proteins in well-preserved ancient human compact bone are still tightly bound to hydroxyapatite and/or collagen. With our solubilization technique, the entrapped ECM proteins are solubilized and identified with special antibodies in Western blot. Our techniques open up more possibilities to diagnose also other infectious diseases and tumors in humans who lived many thousands years ago.